The role of actin cytoskeleton CFL1 and ADF/cofilin superfamily in inflammatory response - Xing, Jianxiao; Wang, Ying; Peng, Aihong; Li, Junqin; Niu, Xuping; Zhang, Kaiming (Frontiers in Molecular Biosciences, 2024)
Actin remodeling proteins are important in immune diseases and regulate cell cytoskeletal responses. These responses play a pivotal role in maintaining the delicate balance of biological events, protecting against acute or chronic inflammation in a range of diseases. Cofilin (CFL) and actin depolymerization factor (ADF) are potent actin-binding proteins that cut and depolymerize actin filaments to generate actin cytoskeleton dynamics. Although the molecular mechanism by which actin induces actin cytoskeletal reconstitution has been studied for decades, the regulation of actin in the inflammatory process has only recently become apparent. In this paper, the functions of the actin cytoskeleton and ADF/cofilin superfamily members are briefly introduced, and then focus on the role of CFL1 in inflammatory response.